(untitled) (Indian Journal of Animal Production and Management, 2024)
A study was carried out to find out the effect of housing on Parasitic load of Nellore Jodipi lambs under tropical environmental conditions. Thirty weaned Nellore ram lambs of 3-4 months age were selected based on body weight and randomly divided into three groups of ten animals each. The parasitic load i.e., Egg per gram (EPG) was determined regularly at every month during entire study period. The faecal egg count was performed by a Mc Master technique. With regard to parasitic load, the prevalence of parasites and eggs per gram (EPG) count were significantly (P<0.05) lower in slatted floor housing system (11.3±3.14) than that of morum floor housing systems (25.6±3.98 and 25.5±3.80). It was concluded that the housing system of elevated slatted flooring with galvalume roofing proved to be effective in controlling reinfestation of parasites and maintain hygiene environment for better performance of Nellore ram lambs.